Comparing the Efficacy of Corneal Collagen Cross-linking and Lamellar Keratoplasty in the Treatment of Keratitis: A Complex Treatment Approach - Kanteti, Krishna Priya (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: 90% of corneal ulcers and other eye injuries resulting in blindness occur in developing nations, and the increase in corneal disorders and eye injuries is correlated with various diagnostic technologies, environmental deterioration, more difficult eye procedures, and an increase in eye infections. This study aimed to evaluate the safety and effectiveness of comprehensive keratitis treatment with both lamellar keratoplasty and corneal collagen cross-linking (CXL). Materials and Methods: The study included 28 patients diagnosed with keratitis who were divided into two groups: the main group (n = 14) and the control group (n = 14). Each patient underwent a comprehensive ophthalmological examination, which included assessments of visual acuity with and without correction, intraocular pressure evaluation, microscopic inspection of the front of the eye, and a thorough examination of the rear of the eye. Results: During the 30–180 days of follow-up, the control group experienced a high rate of post-operative astigmatism in seven (50%) patients, while the main group had a lower rate of three (21.4%) patients. Both groups showed a similar trend in the growth of visual acuity from the 90 to 1095 days of follow-up, with a mean visual acuity of 0.4–0.5 with maximum correction. Conclusion: The application of ultraviolet light during CXL improves the robustness of both the graft and the recipient’s corneal tissue in the suture area. In addition, it directly kills bacteria and viruses, inhibits pathogenic flora, and reduces the risk of recurrent infection.